DONALD TRUMP AND HILLARY CLINTON’S DISTINCTIVE LANGUAGE STYLE DURING THEIR SPEECH ACCEPTANCE - mangantar Sitohang (STIBA IEC JAKARTA, 2016)
This research attempts to analyze the America’s President Nominees for 2017 to 2021 period, Donald Trump and Hillary Clinton’s language styles during their acceptance convention nomination speech seen from Speech Acts classification. Donald Trump representing Republic Party and Hillary Clinton representing Democratic Party must have done their best to prepare their speeches in their first day campaign for all the people coming the building/hall and all American who listen to their speeches. And the fact, the situations/atmospheres in the building, seen from the video/YouTube are so interesting, entertaining, mixed emotional and touching sceneries. Those sceneries are really present not only because their beautiful musical back grounds but above all due to their speech styles relating with or covering not only about their strong claims/beliefs or assertion /descriptions about his/her opponent drawbacks but also about his/her strengths or achievement. The pledges, assertions, commitment and desires or orders articulated are also interesting to see or observe. Many of their utterances contain slippery meanings or messages. So no wonder almost all the people coming the building constantly are really impressed and give enthusiastic and supporting responses to both of them in more than one hour, and quite often they give standing applause after hearing very strong declaration, commitments, plans, vows and promises to all Americans. And apart from that, we can clearly see how each blows his/her blow his/her trumpet or how each attacks his/opponent in world class level. And for the researcher, what they have demonstrated in term of their language styles are important, educating and inspiring, therefore deserves to be observed, and for English language lecturers/teachers and students who have interests in English, this is really interesting to observe